PERAN SELF COMPASSION DALAM MEMEDIASI HUBUNGAN ANTARA FEAR OF FAILURE DENGAN STUDENT ENGAGEMENT - Priyaningtyas, Shafaa Hanuun; Saniatuzzulfa, Rahmah (Universitas Gunadarma, 2024)
Student engagement involves student responsibility in the lecture process which can be influenced by fear of failure, in this relationship there is self-compassion that can bridge. Students with high fear of failure, but high self-compassion make it possible to manage the negative impact of fear of failure and ultimately student engagement increases. This study aimed to determine the role of self-compassion in mediating the relationship between fear of failure and student engagement. The sample in this study was 384 students who were taken using the convenience sampling technique. Data were collected using three scales, namely the student engagement scale, the self-compassion scale, and the fear of failure scale. Data analysis was conducted using mediation analysis with JASP to test the mediating role of self-compassion and PROCESS analysis to see the dynamics of the relationship between the three variables in more detail. The mediation analysis results showed a significant relationship between fear of failure and student engagement in Sebelas Maret University students through self-compassion. The mediating role of self-compassion provides a greater influence than the direct effect. Increasing fear of failure allows a decrease in self-compassion. Furthermore, an increase in self-compassion allows for an increase in student engagement.